The impact of antibiotic selection and interval time among advanced non‐small cell lung cancer patients receiving prior antibacterial treatment and first‐line chemotherapy. (11th May 2022) - Tian, Xiaoman; Mei, Ting; Yu, Min; Li, Yanying; Ao, Rui; Gong, Youling
Abstract: Background: To determine whether antibiotic use before chemotherapy is associated with chemotherapy responses and patient outcomes among NSCLC patients and define the optimal interval between chemotherapy initiation and antibiotic treatment. Materials and methods: One thousand four hundred and four advanced NSCLC patients receiving first‐line platinum‐based doublets therapy were retrospectively analyzed. Kaplan–Meier curve evaluated the impact of antibiotic use and type of antibiotics on the survival of patients. The factors affect the patient's prognosis were further confirmed by Cox regression. The optimal interval between antibiotic treatment and the initiation of chemotherapy was determined by the X‐tile program. Results: NSCLC patients of 33.5% advanced underwent broad‐spectrum antibiotic treatment prior to chemotherapy. In the chemotherapy only (Chemo) and chemotherapy plus antiangiogenesis (Chemo‐angio) treatment groups, prior antibiotic treatment was associated with worse OS (Chemo: 13.8 vs. 17.6 months, p  < 0.001; Chemo‐angio:11.9 vs. 18.1 months, p  = 0.012) and PFS (Chemo: 3.7 vs. 5.8 months, p  < 0.001; Chemo‐angio: 3.1 vs. 5.9 months, p  < 0.001). Cox regression analysis revealed prior antibiotic administration as an independent predictor of OS and PFS (HR for PFS/OS: 1.925/1.452, both p  < 0.001). Antibiotic usage duration (HR for PFS/OS: 1.030/1.036, p  = 0.009/0.001) and type (PFS/OS: p  < 0.001/ p  = 0.01) also showed significant association with patient prognosis, with calculated interval time cutoff values of 2, 4, and 2 days for fluoroquinolones, β ‐lactamase inhibitors, and cephalosporins, respectively. Conclusion: Antibiotic use before first‐line chemotherapy was associated with poor results in advanced NSCLC patients; treatment length and type being strongly correlated with patient outcomes. Appropriate prolongation of the time between two treatments may enhance patient survival. Further prospective research is however necessary. Abstract : In clinical settings, many NSCLC patients undergo antibiotic treatment prior to the initiation of chemotherapy. Previous studies have reported that antibiotic use can affect the efficacy of immunotherapeutic treatment regimens. Whether antibiotics similarly impact chemotherapy efficacy, however, remains to be established. This study compared the effects of different antibiotic treatments on patient prognosis and to define the optimal interval between Abx treatment and chemotherapy initiation.